PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS SEJARAH BERBAHASA ARAB UNTUK PERPUSTAKAAN MADRASAH TSANAWIYAH DI KABUPATEN DEMAK: DEVELOPMENT OF ARABIC LANGUAGE HISTORY-BASED PICTURE STORY BOOKS FOR JUNIOR HIGH SCHOOL LIBRARIES IN DEMAK DISTRICT - Ninda Munaya Sahla; Zukhaira (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
The problem of students' interest in reading, which is still relatively low, does not only occur in reading Indonesian language but also in Arabic. As for the historical story of the Demak Sultanate, the first Islamic Kingdom on the island of Java, which is very interesting to listen to, unfortunately, not many students in Demak Regency know about it. Therefore, researchers developed history-based picture storybooks in Arabic to increase students' interest in reading Arabic. This research uses a research and development design. The results of this research show that teachers and students want history-based picture storybooks in Arabic. The assessment of the validation questionnaire by experts and teachers regarding language appropriateness obtained a score of 3.56. In the aspect of appropriateness of content and material, the score was 3.88. In the aspect of appropriateness of presentation (display), the score was 3.81. Meanwhile, in the aspect of graphic feasibility, a score of 3.80 was obtained.